Bilateral Vestibulopathy in Superficial Siderosis - Lee, Sang-Yeon; Lee, Dong-Han; Bae, Yun Jung; Song, Jae-Jin; Kim, Ji Soo; Koo, Ja-Won (Frontiers in Neurology, 2018)
Background: Superficial siderosis (SS) is a rare condition in which hemosiderin, an iron storage complex, is deposited in neural tissues because of recurrent subarachnoid bleeding. Hemosiderin deposition in the vestibulocochlear nerve (CN VIII), brain, spinal cord and peripheral nerve can cause sensorineural hearing loss (SNHL) and postural imbalance, but much remains unknown about the vestibular manifestations of SS. Objectives: To report the clinical course, cochleovestibular status, and patterns of vestibulopathy during follow-up of a relatively large case series, and to discuss the possible pathophysiological mechanism of vestibular deterioration. Methods: Six patients diagnosed with SS by magnetic resonance imaging (MRI) were enrolled. Their medical records and radiological findings were retrospectively reviewed, particularly in terms of progression of the vestibulocochlear manifestations and the radiological characteristics. Results: All six patients had SNHL. Five of them exhibited progressive hearing loss over years, which was asymmetric in four. On their most recent evaluations, patients showed cerebellar ataxia with combined central and peripheral vestibulopathy on both sides (n = 4), a bilateral peripheral vestibulopathy (n = 1) or isolated central vestibulopathy (n = 1). Notably, the former four patients showed an evolution of isolated central vestibulopathy into combined central and peripheral vestibulopathy. Hypo-intense lesions on T2 weighted MRIs were evident around the cerebellum in all patients, but such lesions were observed around the brainstem in five and the CN VIII in four. The cochlea-vestibular dysfunction generally progressed asymmetrically, but no left-right asymmetry was evident on MRI. Conclusions: SS typically presents as bilaterally asymmetric, progressive cochleovestibular dysfunction with cerebellar ataxia. The pattern of vestibular dysfunction is usually combined central and peripheral vestibulopathy on both sides. Thus, precise identification of audiovestibular dysfunction and central signs is essential in SS, and patients with SS should undergo regular, comprehensive neurotological evaluation to optimize their treatments and prognosis.